2020
DOI: 10.3389/fvets.2020.580007
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anaplasma Variants in Small Ruminants From Central China

Abstract: Anaplasma capra is an emerging zoonotic pathogen that pose a risk to the health of human and veterinary animal. Numerous variants in a variety of domestic and wild animals had been reported since its discovery and confirmation in humans in 2015 and its first detection from goat blood during 2012–2013. In order to find out more A. capra variants data of A. capra in central China, 16S rRNA, gltA, groEL, and msp4 genes of this pathogen were amplified from sheep and goat samples collected during 2011–2015 and phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…(AB509223) detected in serow in Japan in 2009 (Sato et al 2009 ) revealed that they were A. capra . On the other hand, A. capra was detected in 2020 in blood samples taken from goats in 2011 (Zhang et al 2020 ).…”
Section: Introduction (The Great Progress In a Short Time In History ...mentioning
confidence: 99%
“…(AB509223) detected in serow in Japan in 2009 (Sato et al 2009 ) revealed that they were A. capra . On the other hand, A. capra was detected in 2020 in blood samples taken from goats in 2011 (Zhang et al 2020 ).…”
Section: Introduction (The Great Progress In a Short Time In History ...mentioning
confidence: 99%